Bioactive Sphingolipids in Cancer Biology and Therapy - Hannun, Yusuf A.; Luberto, Chiara; Mao, Cungui; Obeid, Lina Marie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents information on both the basic and clinical aspects of sphingolipid-metabolizing enzymes in various cancers. The volume also includes discussions of the innovative techniques and approaches for quantitative analysis and imaging that could significantly impact the general understanding of this topic, and the potential benefit of targeting sphingolipid enzymes to develop novel cancer therapeutics. As well, the volume includes a critical examination of the specific pathways and pathobiologies associated with the altered regulation of sphingolipid metabolism as a contributor to the development and/or maintenance of pathological conditions such as cancer.
Keywords: Medicine; Cancer research; Laboratory medicine; Biochemistry; Biomedicine; Cancer Research; Biochemistry, general; Laboratory Medicine; Electronic books